Role of Local Institution and Indigenous Knowledge Linkages in Overcoming the Problem of Hybrid Corn Seeds in Remote Area - Bahtiar; Darmawan Salman; Muhammad Azrai; A. Tenrirawe; Putra Astaman (Indigenous Agriculture, 2023)
The role of local institution linkage greatly determines the sustainability of the national hybrid corn seed production system. Linking and integrating indigenous knowledge and local institution in one program is necessary to support an efficient and effective work system. This study analyzes the linkages between institutions and indigenous knowledge that support the smooth supply of hybrid corn seeds for farmers in remote areas. Using Interpretative Structural Modeling analysis to map institutions into four quadrants (Dependent, Linkage, Autonomous, and Independent). Involved three experts in defining the institutions that play a role in the seed system: government, seed producers, and researchers. The results showed that 19 institutions played an active role, 6 of which were in the Independent quadrant, 9 in the linkage quadrant, 6 in the dependent quadrant, and none in the autonomous quadrant. This means that the identification of related institutions by experts is correct. Based on this mapping, 4 institutions have a very large influence on the development of the corn seed system, namely the Indonesian House of Representatives (IHR), the Planning Bureau (PB), the Directorate General of Food Crops (DGF), and the Seed Certification Inspection Center (SCIC). That institution can encourage the advancement of hybrid corn seed production systems. However, their dependence on external environmental influences is still high, so their independence is relatively low. Then the institutions that must be conditioned that they still have high Driving Power and Dependence Power are the Agency for Agricultural Research and Development (AARD), the National Seed Company (NSC), the Seed Grower Group (SGG), the Governor (GV), and the Provincial Agricultural Services (PAS). That institution only needs maintenance to continue excelling in providing farmers with corn seeds. The role of local institutions and indigenous culture (LG, EWF, EAO, and LFG) have not been seen to be involved in strengthening the seed system even though its independence is very high, so it is feared that the seed system is unsustainable.